2018
DOI: 10.1007/s10803-018-3829-x
|View full text |Cite
|
Sign up to set email alerts
|

Atypicalities of Gesture Form and Function in Autistic Adults

Abstract: While well-represented on clinical measures, co-speech gesture production has never been formally studied in autistic adults. Twenty-one verbally fluent autistic adults and 21 typically developing controls engaged in a controlled conversational task. Group differences were observed in both semantic/pragmatic and motoric features of spontaneously produced co-speech gestures. Autistic adults prioritized different functions of co-speech gesture. Specifically, they used gesture more than controls to facilitate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 56 publications
2
30
1
1
Order By: Relevance
“…Some researchers have proposed that task design differences may result in variations across studies in language development, including narrative productions and gestural skills (Berman, 2004;Stirling et al, 2014). For example, de Marchena et al (2019) found that participants in the ASD group used some types of gestures more often than those in the TD group in a collaborative referential communication task. These gestures were used to regulate turn-taking, which is not included in a storytelling task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have proposed that task design differences may result in variations across studies in language development, including narrative productions and gestural skills (Berman, 2004;Stirling et al, 2014). For example, de Marchena et al (2019) found that participants in the ASD group used some types of gestures more often than those in the TD group in a collaborative referential communication task. These gestures were used to regulate turn-taking, which is not included in a storytelling task.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the difference in the categories of gesture type is common. Apart from the gesture types used in this study, some researchers use categories including descriptive gestures, symbolic gestures, interactive gestures, and numerical gestures (Ingersoll, 2007;de Marchena et al, 2019). These differences in definition and characterization make it difficult to compare results across studies and to reach an agreement.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that difficulties related to prosody (Globerson et al, 2015;, changes in gesture communication (de Marchena et al, 2019), semantic and pragmatic skills (Trevisan & Birmingham, 2016), in the metaphorical comprehension of some sentences and expressions and the incessant speech about a favorite subject (Klin, 2006), can interfere in the establishment of social relations and, although these characteristics should not be generalized, all students should be contemplated in their singularities in an educational proposal that adjectives itself as inclusive. In this regard, we can reflect that bullying, present in the reports of all participants and observed in the three meaning cores, may be more related to stigma and social rejection associated with a given condition of disability (disabilities) and not to characteristics of the ASD itself (McLeod, Meanwell, & Hawbaker, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gestures have also been overlooked in research on figurative meaning in ASD, even though difficulties using and understanding gestures have long been considered to be central to ASD. Such difficulties are, in fact, part of the diagnostic criteria for the disorder (DSM-5, American Psychiatric Association, 2013;de Marchena et al, 2019;Eigsti & de Marchena, 2017). Littlemore argues that more studies are needed of embodied metaphor production by individuals with ASD and, moreover, that such studies require "a strong focus on the use of gesture" (2019, p. 175).…”
Section: D a T A T Y P E Smentioning
confidence: 99%
“…A multimodal approach is also pertinent in research on ASD because it has been suggested that at the core of ASD are problems with integration across modalities (de Marchena & Eigsti, 2010;Eigsti, 2013;Kana et al, 2006). In fact, it has been proposed that "integrating across modalities in both production and comprehension may be one [of] the greatest communication challenges faced by autistic people" (de Marchena et al, 2019(de Marchena et al, , p. 1451. Multimodal studies that take a usage-based approach by considering authentic communication, in line with what we propose, can potentially offer valuable complementary insights to, for example, neuroimaging studies and cognitive testing.…”
Section: D a T A T Y P E Smentioning
confidence: 99%